Financial Risk of Airlines in Indonesia Case Study of Kualanamo (Medan) to Soekarno-Hatta (Cengkareng) Flight Route - Edward Sirait (Jurnal Indonesia Sosial Sains, 2024)
This reseach aims to identify and analyze the financial risks faced by airlines in Indonesia, with a particular focus on the Kualanamo (Medan) to Soekarno-Hatta (Cengkareng) flight route. Using a case study approach, the study evaluated a range of factors influencing financial risk, including fluctuations in fuel prices, currency exchange rate volatility, market competition, and regulatory changes. Data was collected through interviews with airline financial managers, analysis of financial statements, and review of related literature. The results showed that fluctuations in fuel prices and exchange rates are the main factors contributing to financial risk. In addition, intense competition and regulatory changes have also had a significant impact on the airline's financial stability. This research provides recommendations for risk mitigation strategies that airlines can implement to improve their financial resilience. The implications of these findings are expected to assist financial managers and policymakers in designing more effective policies to manage financial risks in the aviation industry.